Comparative Study between Colloid versus Crystalloid Solutions during Spinal Anesthesia for Elective Cesarean Section - Faez Mahdi; Hiwa Saber; Ziwar Ahmed (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Background: One of the most dangerous complications for mother and baby during cesarean section ishypotension due to spinal anesthesia. Several methods are used to prevent and treat hypotension, the safest of whichis fluid replacement. This study aimed to compare the effectiveness of colloidal solutions and crystalloid solutions inpreventing hypotension resulting from spinal anesthesia during elective cesarean sections, along with assessing therequirement for vasopressors to treat severe hypotension due to the spinal anesthesia.Methods: This prospective comparative study was conducted in Erbil Maternity Teaching Hospital fromMay 2021 until October 2021. Two groups of 35 patients were prepared for elective cesarean section, crystalloid groupreceived normal saline, while the colloid group received voluven infusion. Systolic blood pressure, diastolic bloodpressure, and the need for vasopressors (a combination of ephedrine plus phenylephrine) were compared between thegroups.Results: There is no statistically significant difference in the prevalence of hypotension between the two groups(p-value>0.05), except at 5min, there was significant hypotension (p-value<0.0001 in the crystalloid group and p-value<0.003 in the colloid group). However, there is less need for vasopressor drugs to treat hypotension in the colloidgroup (p-value<0.001).Conclusion: Both colloidal and crystalloid solutions have been effective in preventing hypotension due to spinal anesthesia in elective cesarean section. However, compared to the crystalloid group, in the colloidal infusion group, there isless need to use vasopressor drugs to treat hypotension.